Self-determined Occupational Performance Model for Children From Economically Disadvantaged Backgrounds. (December 2021) - Bray, Laura M.P.; Capilouto, Gilson
Background . Children from low-income backgrounds have a higher incidence of handwriting challenges due to the unique social and environmental stressors associated with poverty. Additionally, children from economically disadvantaged households are at risk for motor, cognitive, and social deficits, which further impact their handwriting performance.Purpose . The purpose of this paper is to propose a theoretical model that provides a holistic perspective for addressing the handwriting needs of children from low-socioeconomic backgrounds.Key Issues . The presented conceptual model is derived from the person–environment–occupation model for occupational performance and self-determination theory. These theories reciprocally complement and enhance each other, providing a foundation from which clinicians can guide evaluation and intervention.Implications . Through the use of the proposed model, evaluation and intervention focus on intrinsic motivation while considering the physical, social, and cultural impacts on a child's occupational performance. The provider connects with the child's basic psychological needs, thus improving handwriting outcomes and facilitating improved academic performance.